Issues in applications of nursing care robots, and in the training of care workers in their use in Japan - Nguyen, Nghia Chi; Saito, Masami (Frontiers in Medicine, 2025)
IntroductionAlthough Information and Communication Technology (ICT) care robots are being used to address the shortage of human resources in nursing care in Japan, there are few studies on the application and disadvantages of robotics in caring for older persons.MethodsThe authors surveyed seven students taking a nursing care course based on a self-administered questionnaire after they experienced various ICT nursing care robots in the education program. The responses were coded and analyzed qualitatively to consider the advantages and disadvantages of using robots in nursing care and the roles of nursing care workers.ResultsWhile nursing care robots have been evaluated for their contributions to caring for older persons, they also have disadvantages, such as high cost, discomfort, and risk of injury.ConclusionEducation programs for welfare students should include active experience with robots and a deep understanding of their advantages and disadvantages in caring for older people. Further collaboration between development companies, training schools, and care sites is essential to help educators and students get used to nursing care robots soon, refer to their experience in testing these robots, and simultaneously study potential disadvantages and discomforts of nursing care robots.